Anisotropy-based mechanism for zigzag striped patterns in magnetic thin films - Billoni, Orlando Vito; Bustingorry, S.; Barturen, M.; Milano, J.; Cannas, Sergio Alejandro (2022)
Fil: Billoni, Orlando Vito. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía y Física; Argentina.